The correlation between delirium subtypes and treatment efficacy and biochemical parameters: A preliminary study - Gürok, Mehmet Gürkan; Kazgan, Asli; Kaya, Mehmet Onur; Atmaca, Murad (My University, 2019)
Aim: Delirium is one of the most important emergency cases in geriatric patient population with high morbidity and mortality rates.In clinical practice, three delirium types are defined as hyperactive, hypoactive and mixed according to the psychomotor activity andthe level of wakefulness. In the present study, the purpose was to examine the treatment response of the subtypes of delirium andits relation with possible biochemical parameters.Material and Methods: Thirty patients, who were diagnosed with delirium and who were hospitalized for treatment were included inthe present study. Following the classification of the patients according to the subtypes of delirium, they were evaluated before thetreatment and on the 7th day of the treatment. In both interviews, the Delirium Rating Scale (DRS), Richmond Agitation and SedationScale (RASS), and Memorial Delirium Rating Scale (MDRS) were applied to the patients. In addition, the biochemical parameters thatwere required for the patients in relevant clinics were recorded.Results: Delirium patients consisted of a total of 30 patients. The patients of all three subtypes of delirium responded to the treatmentscores at significant levels in terms of scale scores. However, when the Hyperactive, Hypoactive and Mixed subtypes were evaluatedin terms of the difference of change on the 1st and 7th days of the treatment separately, it was determined that the difference ofchange values were significantly higher in the hyperactive type in terms of RASS, DRS and MDRS (p=0.004; p=0.002; p=0.001,respectively).Conclusions: As a result, the findings of the present study showed that patients who are diagnosed with delirium might show differenttreatment responses according to motor subtypes. Further studies are required to be conducted with bigger sampling groups.
Keywords: Genel ve Dahili Tıp